Software engineering design : theory and practice - Otero, Carlos E. (Applied software engineering series., 2012)
... Intended for use as a textbook for an advanced course in software design. Each chapter ends with review questions and references. ... provides an overview of the software development process, something that would not be out of line in a course on software engineering including such topics as software process, software management, balancing conflicting values of stakeholders, testing, quality, and ethics. The author has principally focused on software design though, extracting the design phase from the surrounding software development lifecycle. ... Software design strategies are addressed, inclu.